Phonological Competence and Arabic Speaking Proficiency among MTs Students: A Quantitative Correlational Study: Kompetensi Fonologis dan Kemahiran Berbahasa Arab di Kalangan Mahasiswa MTs: Sebuah Studi Korelasi Kuantitatif - Raudhatul Jannah H. Genti; Ratni Bt. Hj. Bahri; Janet Watson (Language Development Center, 2026)
Background: Arabic language learning in Indonesian madrasahs faces persistent phonological challenges because several Arabic phonemes, particularly /ع/, /ح/, and /ق/, do not exist in Indonesian and many local Austronesian languages. These differences often affect students’ pronunciation accuracy and oral intelligibility in Arabic communication. Purpose: This study aimed to examine the relationship between Arabic phonological competence and Arabic speaking proficiency among seventh-grade students at MTsN 2 Boalemo. Method: A quantitative correlational design was employed. The participants consisted of 60 students selected through proportional stratified random sampling from a population of 140 seventh-grade students. Data were collected using two validated instruments: the Arabic Phonological Competence Test (TKFBA) and the Arabic Speaking Proficiency Test (TLKB), both scored on a 0–100 scale. Students’ oral performances were audio-recorded and evaluated by trained raters. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, ANOVA-based linearity testing, Pearson correlation, and simple linear regression with IBM SPSS Statistics 28 at a significance level of α = .05. Results and Discussion: The findings revealed a statistically significant positive relationship between Arabic phonological competence and Arabic speaking proficiency (r = .999, p < .001). Regression analysis indicated that phonological competence was strongly associated with variation in speaking proficiency scores (R² = .998). These findings support previous studies emphasizing the importance of phonological competence in second-language speaking performance and contribute empirical evidence from the underrepresented context of Arabic language learning in Eastern Indonesia. Nevertheless, the exceptionally high coefficient values should be interpreted with caution and warrant further verification through replication studies involving larger and more diverse samples. Conclusions and Implications: The study concludes that Arabic phonological competence is strongly associated with Arabic speaking proficiency among MTs students. Therefore, phonological training should be systematically incorporated into Arabic language instruction, particularly for phonemes that present difficulties for Indonesian learners. Future research is encouraged to employ longitudinal or experimental designs to further investigate the role of phonological competence in speaking development.